Penyelesaian Sengketa Pajak Perusahaan Modal Asing di Indonesia - S. Endang Prasetyawati (KEADILAN PROGRESIF, 2017)
The problem of disputes in foreign business practices that occur is among foreign investors as taxpayers on the one hand with the government or the Director General of Taxation as tax authorities or tax collectors on the other side. The problem in this research is how to solve the dispute of foreign capital companies in Indonesia. The problem approach in this research is the normative juridical approach that is approach by way of reviewing the rules related to the problem to be discussed. After data is collected and processed, then analyzed qualitatively. The result of the research shows that the completion of the objection process to the Director General of Taxes does not provide legal protection and justice to the taxpayer (PMA Company) because the process of the objection is the disputing party (DGT). While the appeal through the Tax Court is doubtful of its independence and objectivity because the judges in the Tax Court are from former officials of the Directorate General of Taxes of the Ministry of Finance and the administration, financial and human resources management in the Ministry of Finance. Meanwhile, the Review to the Supreme Court did not provide certainty of the settlement time.